THE IMPORTANCE OF TEACHER ETHICS ON STUDENTS’ MORAL DEVELOPMENT - Pratama, Agus; Syaputri, Sindy; Mahesa, Rahman; Pulungan, Annisa Fauziah; Nasution, Muhammad Rafly (Proceeding International Seminar of Islamic Studies, 2023)
The increasingly widespread changes in mentality and morality in students today are due to internal and external factors so that these students lack self-awareness when they commit bad deeds against those around them. This happens because of the lack of moral education to students. Therefore, moral education needs to be implemented in the education system to overcome this problem. What's more, teachers as parents of second students have an important role in the moral education of their students to create young people who have good morals.The purpose of this research is for educators to improve good and proper ethics as role models for their students to emulate in social life. This study uses a qualitative research method of library research (library research). The results of this study are that educators must train themselves to apply good ethics to their students because students will tend to imitate the behavior of their teachers. These ethics are like being fair, attractive, more democratic than autocratic, having a sense of humor, and being able to interact well with students both individually and in groups. In conclusion, the teacher is a leader for himself and for the students he teaches, so educators should be good role models for their students so that students who have good morals are formed.